Formal consumption in the contemporary industrial product (Journal of the College of Basic Education, 2022)
The research tagged with (formal consumption in the contemporary industrial product) was concerned with studying the phenomenon of formal consumption, the reasons for its appearance, the factors affecting it, and how to avoid formal monotony to come up with new forms far from the ordinary. contemporary industrial product